Transanal hemorrhoidal dearterialization versus stapled hemorrhoidectomy in the treatment of hemorrhoids: A PRISMA-compliant updated meta-analysis of randomized control trials. Issue 29 (July 2018) - Song, Yan; Chen, Honglei; Yang, Fang; Zeng, Yuheng; He, Yongheng; Huang, Huiyong
Abstract: Background and Objective: The aim of this study was to compare the outcomes of transanal hemorrhoidal dearterialization (THD) and stapled hemorrhoidectomy (SH) in the treatment of hemorrhoids by a meta-analysis. Methods: Randomized control trials (RCTs) comparing SH with THD were searched for in databases, including MEDLINE, PubMed, Web of science, Embase, and the Cochrane Library database. Data were independently extracted from each study, and a meta-analysis was performed using RevMan5.2 software. Results: Eight RCTs, including 977 patients, were included in this meta-analysis. No statistically significant differences were noted between THD and SH in terms of total complications (OR, 0.93; 95% CI, 0.69, 1.25), but a significant differences were noted in terms of bleeding (OR, 1.85; 95% CI, 1.10, 3.10). The total recurrence rate was higher in THD than in SH on short-term follow-up; however, the recurrence rate was equal in both the THD and SH groups on long-term follow-up. The present study showed that no significant difference between SH and THD in terms of postoperative pain (OR, 0.43; 95% CI, −0.43, 1.29), operative time (OR, −3.12; 95% CI, −7.01, 0.77), hospital time (OR, −0.00; 95% CI, −0.21, 0.20), time before returning to work (OR, -0.50; 95%CI, −4.42, 3.43), and reoperation rate (OR, 1.81; 95% CI, 0.93, 3.54). Conclusion: Our meta-analysis indicated that THD and SH are equally effective techniques for the treatment of hemorrhoids. However, future studies addressing cost-effectiveness, satisfaction rate, and recurrence rate over a long follow-up period are needed to validate these results.